Collaborative Learning: A Model of Strategies to Apply in University Teaching - Roselli, Nestor Daniel (2017)
Collaborative learning is a construct that identifies a strong field nowadays, both traditional on-site and virtual education. The article aims to present a model of strategies that teachers can implement to develop sociocognitive collaboration. These strategies are classified according to the socio-cognitive aspect they aim at. It must be taken into account that all the strategies are thought to be applied in on-site classes, but it is possible to adjust them to be virtually applied, using the different communicational technologies. Each strategy is specifically described. These strategies refer to six areas: encouragement of dialogue, listening to others and reciprocal/mutual evaluation; collaboration for negotiation and consensus building; activity organization; study and appropriation of bibliographic information; conceptual development; collective writing. Finally, conclusions and recommendations for the implementation of these strategies are discussed.